شعرية المقدمة في الرحلة الادبية العراقية بعد 2003 - خيري فاهم, شيماء; ساطع, زينب (Journal of College of Education, 2019)
The literary journey of the author moves to a place other than the first place is a literary spatial excellence and lead the place in the journey the most important corner in the writing of the text of the trip, and any text must have steps and parts studied to be effective and successful text and obtained the degree of acceptance and satisfaction of readers, , And after the inventory and extrapolation of the literary trips that I have collected, which amounted to (50) journeys, I found that the introduction may be personal only the traveler writes his introduction according to his view and vision of travel and moving from one country to another without extravagance in praise of the trip and there is a second type of introductions, Another by nomads In addition to the introduction written by the traveler himself, the other provider may be a poet or a novelist or only a friend reader, and the introduction of heterosexual is usually a container on the praise of the traveler and printing in addition to the praise of the journey and the entity and nature of narration, either poetic not specifically follow the character of the writer and the poetry of his journey, The personality of the provider and his literary ability so the introduction written by a writer or poet more poetic than those written by a friend or journalist, and in both cases in the introduction plays its role as a detailed identification identity of the trip and its narrative